Volumetric geochemical modeling of gold objects on the example of deposit Chertovo Koryto (Patom upland) - Roman Gavrilov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the study is caused by the need to improve the efficiency of exploration work on the gold ore through the creation of predictive models of known deposits and their comparison with promising targets. The main aim of the research is to create a bulk geochemical field model to develop the forecasting and prospecting criteria of gold mineralization. Research methods: geochemical mapping, mathematical processing of the results of geochemical work, modeling of geochemical fields by the methods of multivariate statistics, geological and genetic interpretation of geochemical data Results. It was ascertained that gold and trace elements distribution in the field volume does not fit any known distribution laws. The most contrasting anomalies in high-volume metasomatic aureole are created by Au, As, Ag and Pb. The applied complex of techniques for processing geochemical information helped to decipher the abnormal structure of geochemical field. The mineralized zone is located in the center of large-volume metasomatic aureole, coinciding in space with high contrast Co-Ni, Ag-Pb-Zn-Cu and As geochemical associations. The contours of the mineralized zone are mapped by Co-Ni and Ag-Pb-Zn-Cu geochemical associations, and its central part is mapped by As association. Analysis of geochemical associations distribution showed that the concentric-zonal structure is typical for large-volume metasomatic aureole. Distribution of geochemical associations fits the staging of hydrothermal mineralization set in the field. It is obvious that the formation of three geochemical associations indicates a difference in conditions and time of formation of orebearing solutions. Using mining and geological program Datamine studio 3 the author has made the bulk geochemical model of the deposit. The model of gold deposit may contribute to allocation of potentially interesting objects.